The impact of Christian educational and socio-ethical interventions in preventing youth kidnapping in Lagos - Ayotunde, Olulowo Segun; Solomon, Taiwo Babawale; Israel, Adedeji Olusola (Postgraduate Program of State Islamic University (UIN) Salatiga Jl. Lingkar Salatiga Km. 02 Salatiga, Indonesia https://pps.uinsalatiga.ac.id/, 2024)
The mentality of kidnapping for ransom among youths is a contemporary social challenge in Lagos State, South Western Nigeria. If this issue is not addressed, it will negatively impact people psychologically, emotionally, economically, politically, socially, and morally. The purpose of this study is to examine the effect of Christian education on youths' behavioural training and investigate how ethical training provided by churches can contribute to the reduction of kidnapping incidents among youths. The study employed a descriptive quantitative method, gathering data from 120 respondents, including Christian students, mature adults from the University of Lagos, and church members from various denominations across Lagos State. Twelve churches were purposively selected to represent different denominations. The questionnaire comprised 15 items under two sections: demographics and Christian ethics in behavioural training and kidnapping prevention. Responses were measured using a 4-point Likert scale (strongly agree, agree, disagree, strongly disagree). A total of 116 completed questionnaires were analysed, representing a return rate of 96.7%. Quantitative analysis included descriptive statistics such as frequency count, percentages, mean, and standard deviation. The results show that Christian education training, the adoption of societal ethical values, and the promotion of character transformation leading to responsible decision-making are significantly correlated with the decrease in youth kidnappings in Lagos State. The study advocates for early, proactive, and consistent teaching of Christian values and rules, encouraging the use of ethical tools such as reward and punishment to motivate selfless and good decision-making by youths.